(untitled) (Nepalese Journal of Ophthalmology, 2013)
Introduction: Color Doppler Imaging (CDI) is used widely to study retrobulbar circulation. Objectives: To determine the association between progression of diabetic retinopathy (DR) and alterations in retrobulbar arterial circulation using CDI studies. Materials and methods: Prospective observational case series. It is single institutional study of 50eyes of nonproliferative diabetic retinopathy in 50 patients with type II diabetes mellitus. DR was graded according to ETDRS system. Retrobulbar circulation was studied in patients for Peak systolic velocity (PSV), End diastolic velocity (EDV) and Resistive index (RI) in Central retinal artery (CRA), Ophthalmic artery (OA) and Posterior ciliary artery (PCA) using CDI initially and reevaluated after 6 months or later for any change in retinopathy grade and arterial circulation parameters. The patients were grouped as Group I not showing progression of DR and Group II showing progression. The two groups were compared for any significant change in CDI parameters. Results: The baseline resistive indices were higher than normal population. There was significant increase in RI in PCA and CRA in all patients after 6 months. 14 patients (28%) showed progression of DR and 36 (72%) did not show progression of DR. There was no significant association with progression of retinopathy and CDI findings. (p=>0.05). Conclusion: The retrobulbar arterial circulation seems to be affected in all diabetics with DR. The changes appear to be progressive. The CDI findings in arterial circulation however lack predictive power for progression of diabetic retinopathy in non proliferative DR. Nepal J Ophthalmol 2013; 5(10): 147-153 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8705